YOUTH MOBILIZATION IN THE 2019 ELECTION CAMPAIGN IN WEST JAVA, INDONESIA (STUDY OF THE GERINDRA PARTY, THE INDONESIA DEMOCRATIC PARTY OF STRUGGLE, AND THE PROSPEROUS JUSTICE PARTY) - Witianti, Siti; Paskarina, Caroline; Solihah, Ratnia (JWP (Jurnal Wacana Politik), 2025)
West Java has the largest number of voters including young elections, but there are symptoms where political parties have rarely been placed as subjects in elections by political parties. This study aims to describe the strategies of the Gerindra Party, PDIP, and PKS in mobilizing youth support in the 2019 elections in West Java and to analyze research phenomena based on the theory used so that it is hoped that new concepts will be obtained in mobilizing youth support during the election momentum, especially in implementing strategies mobilization that places the youth segment as a political subject, not only as an object of party strategy. The research method in this study used qualitative methods and descriptive techniques including literature review and in-depth interviews with party members and youth activists,. The research results show that in the 2019 Election the Gerindra Party, PDI Perjuangan, and PKS used several strategies in mobilizing youth support. However, not all strategies are carried out optimally. For example, the PKS does not utilize volunteers or its party wings in mobilizing youth due to differences in views within political parties, the use of mass media is not yet optimal, as well as the use of election data in formulating strategies is not optimal.